Electoral dynamics and behavior in Mexico City: case of the Pedregal de Santo Domingo neighborhood, 2012-2018 - Lizama Carrasco, Guillermo (2023)
Pedregal de Santo Domingo is one of the most populated and emblematic neighborhoods in the Coyoacán municipality (Mexico City). This article shows the electoral behavior of the neighborhood and the local government through a statistical and geographical analysis that includes the federal electoral processes of 2012 and 2018 that elected president, senators, and deputies. The information comes from the Electoral Institute of Mexico City and confirms the centre-left tradition (a historical feature in this area), even if it transits from the Party of the Democratic Revolution (PRD) to the National Regeneration Movement (Morena). This change implied an increase in electoral competition and political fragmentation that explains the dynamism that characterizes urban spaces in the electoral sphere. This article considers that social space replicates electoral behavior, an idea that feeds into the sociological theory of voting.